The Possibility of an Island - Laudo, Alexandra; Anglès, Magda; Gallardo, Gemma (Barcelona : Fundació Joan Miró, 2018)
Ortín, Gerard ; de Andrés, Irene ; Pino, Lucía C. ; Sánchez Barroso, Bárbara ; Gideonsson/Londré
boek